Morphological image normalization based on the method of section - Zroychikova, O. (ХНУРЕ, 2011)
The given work is devoted to consideration and studying the actual problem of the image normalization. It is assumed that the image is distorted by affine transformations. To solve this problem it is used method of sections and operations of mathematical morphology.
Keywords: image; morphology